Предмет: Математика,
автор: lizalimon
Задание 4.27. Помогите,пожалуйста)))
Приложения:
Ответы
Автор ответа:
0
11)-b/[a(a-3)(a+3)]-1/[a(a+3)]+3/[a(a-3)(a+3)]=(-b²-ab+3b+3a)/[ab(a²-9)]=
=[3(a+b)-b(a+b)]/[ab(a²-9)]=(a+b)(3-b)/[ab(a²-9)]
2)(a+b)(3-b)/[ab(a²-9)] *ab(a²-9)/(3-b)²=(a+b)/(3-b)
a=3,b=2 (3+2)/(3-1)=5/1=5
=[3(a+b)-b(a+b)]/[ab(a²-9)]=(a+b)(3-b)/[ab(a²-9)]
2)(a+b)(3-b)/[ab(a²-9)] *ab(a²-9)/(3-b)²=(a+b)/(3-b)
a=3,b=2 (3+2)/(3-1)=5/1=5
Автор ответа:
0
Sedinalana,Всё понятно)Спасибо)Только есть один вопрос: почему b²-6b+9 стало (3-b)²,а не (b-3)²?
Похожие вопросы
Предмет: Математика,
автор: VaDimka222345
Предмет: Химия,
автор: krillvasilev
Предмет: Другие предметы,
автор: pvuafanasieva
Предмет: Математика,
автор: Shark120042
Предмет: Литература,
автор: hasnter2000